JUMLAH OSTEOBLAS PADATULANG FEMUR TIKUS PUTIH PASCA IMOBILISASI DENGAN METODA PIN DAN XENOGRAFT - , WHANA ANGGIASARI, Dr. drh. Dhirgo Adji, M.P. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Fracture is a break in the continuity of bone either totally or partially. Treatment of bone fractures can be performed with xenograft bone grafting. Xenograft is a bone graft material derived from another species. Xenograft function in fracture healing is as osteoinduction. Osteoinduction is stimulated by factors contained in graft material includes proteins and growthfactors. Proteins and growth factors that are contained in the graft material relating to the formation of osteoblasts. This study aims to determine the change of the number of osteoblasts on bone fractures after switching performed by xenograft. Sixteen Sprague-Dawley rats divided into two groups. The first group of rats in an operation to break a brokenfemur os up to 60%. The second group of rats in an operation to break a femur osup to 100% and then treated with bone grafting using a xenograft. Histopathological observation of the change in the number of osteoblasts performed on bonefracture after 24 hours, one week, two weeks, and four weeks. The results showed that the number ofosteoblasts in bone fractures with post-grafting xenograft significantly increased compared with the number of osteoblasts in bone after fracture without grafting.